2019
DOI: 10.1074/jbc.ra119.009432
|View full text |Cite
|
Sign up to set email alerts
|

Compromised function of the ESCRT pathway promotes endolysosomal escape of tau seeds and propagation of tau aggregation

Abstract: Supporting Information: Figure S1 Figure. S1 -Endogenous tagging of endolysosomal compartments (A) Representative fluorescence microscopy images of CRISPRi-HEK293T cells with RAB7A-mNG 11 endogenously labeled with the split-mNeonGreen system. Cells were treated with AF555-tau fibrils for 22 hours. (B) Representative fluorescence microscopy images of HEK293T cells with mNG 11 -RAB7A (top) or LAMP1-mNG 11 (bottom) endogenously labeled with the split-mNeonGreen system.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
99
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 129 publications
(108 citation statements)
references
References 70 publications
9
99
0
Order By: Relevance
“…Following established protocols for validation of primary screens, we targeted each gene with two distinct sgRNAs. 2022 We found that depletion of 6/7 (86 %) of the hits identified from the “high”/”low” and 1/2 (50 %) of the hits from the “medium”/”low” gave rise to phenotypes consistent with the pooled screen result (Fig. 3b, S3b-c).…”
Section: Resultssupporting
confidence: 78%
“…Following established protocols for validation of primary screens, we targeted each gene with two distinct sgRNAs. 2022 We found that depletion of 6/7 (86 %) of the hits identified from the “high”/”low” and 1/2 (50 %) of the hits from the “medium”/”low” gave rise to phenotypes consistent with the pooled screen result (Fig. 3b, S3b-c).…”
Section: Resultssupporting
confidence: 78%
“…To learn more about the steps between uptake of tau seeds and subsequent aggregation, Chen et al use their modified FRETbased tau aggregation assay in a CRISPRi-based screen to identify regulators of tau uptake and propagation. They first confirmed that they could observe a prion-like propagation of tau aggregation within the cell using seed material of recombinant aggregated tau or aggregates purified from AD patient brains (7). As in previous studies, the authors observed tau uptake into the cell, presumably via endocytosis, followed by release into the cytosol, where propagation of tau aggregation occurs.…”
supporting
confidence: 68%
“…The strict requirement for Draper in ORN-to-glia and ORN-to-glia-to-PN aggregate transfer indicates that neuronal mHtt ex1 and glial wtHtt ex1 proteins physically interact during or following phagocytic engulfment, requiring breaching of one or more membrane barriers that normally exclude phagocytosed material from the glial cytoplasm. In support of this, prion-like aggregates formed by α-synuclein, tau, and mHtt ex1 have the capacity to rupture cell surface or endolysosomal membranes to directly access the cytoplasmic compartment (Chen et al, 2019; Falcon et al, 2018; Flavin et al, 2017; Zeineddine et al, 2015). It is also possible that phagocytosis becomes dysregulated in diseased or aged brains.…”
Section: Discussionmentioning
confidence: 90%
“…Accumulating evidence supports the idea that intracellular aggregates formed by tau, α-synuclein, TDP-43, SOD1, and mutant huntingtin (mHtt) transfer from cell-to-cell and self-replicate by recruiting natively-folded versions of the same protein, analogous to how infectious prion protein (PrP Sc ) templates the conformational change of soluble PrP C in prion diseases (Vaquer-Alicea and Diamond, 2019). Numerous studies have pointed to roles for endocytosis and exocytosis (Asai et al, 2015; Babcock and Ganetzky, 2015; Chen et al, 2019; Holmes et al, 2013; Lee et al, 2010; Zeineddine et al, 2015), membrane permeabilization (Chen et al, 2019; Falcon et al, 2018; Flavin et al, 2017; Zeineddine et al, 2015), tunneling nanotubes (Costanzo et al, 2013; Sharma and Subramaniam, 2019), and neuronal activity (Wu et al, 2016) in entry and/or exit of pathogenic protein assemblies from cells, but the exact mechanisms by which amyloid aggregates or on-pathway intermediates could cross one or more biological membranes in the highly complex central nervous system (CNS) remain an enigma.…”
Section: Introductionmentioning
confidence: 99%